Applying Evidence-Based Medicine Principles to Hip Fracture Management - Bernstein, Joseph; Morshed, Saam; Helfet, David L.; Bhandari, Mohit; Ahn, Jaimo (Frontiers in Surgery, 2014)
Bone has the capacity to regenerate and not scar after injury—-sometimes leaving behind no evidence at all of a prior fracture. As surgeons capable of facilitating such healing, it becomes our responsibility to help choose a treatment that minimizes functional deficits and residual symptoms. And in the case of the geriatric hip fracture, we have seen the accumulation of a vast amount of evidence to help guide us. The best method we currently have for selecting treatment plans is by the practice of evidence-based medicine. According to the now accepted hierarchy, the best is called Level I evidence (eg, well performed randomized controlled trials)—but this evidence is best only if it is available and appropriate. Lower forms of accepted evidence include cohort studies, case control studies, case series and case reports, and last, expert opinion--all of which can be potentially instructive. The hallmark of evidence-based treatment is not so much the reliance on evidence in general, but to use the best available evidence relative to the particular patient, the clinical setting and surgeon experience. Correctly applied, varying forms of evidence each have a role in aiding surgeons offer appropriate care for their patients--to help them best fix the fracture.